Light‐Induced Conformational Changes in the Plant Cryptochrome Photolyase Homology Region Resolved by Selective Isotope Labeling and Infrared Spectroscopy1. (May 2017) - Sommer, Constanze; Dietz, Marina S.; Patschkowski, Thomas; Mathes, Tilo; Kottke, Tilman
Abstract: Plant cryptochromes are photoreceptors that regulate flowering, circadian rhythm and photomorphogenesis in response to blue and UV‐A light. It has been demonstrated that the oxidized flavin cofactor is photoreduced to the neutral radical state via separate electron and proton transfer. Conformational changes have been found in the C‐terminal extension, but few studies have addressed the changes in secondary structure in the sensory photolyase homology region (PHR). Here, we investigated the PHR of the plant cryptochrome from the green alga Chlamydomonas reinhardtii by light‐induced infrared difference spectroscopy in combination with global 13 C and 15 N isotope labeling. Assignment of the signals is achieved by establishing a labeling strategy for cryptochromes that preserves the flavin at natural abundance. We demonstrate by UV/vis spectroscopy that the integrity of the sample is maintained and by mass spectrometry that the global labeling was highly efficient. As a result, difference bands are resolved at full intensity that at natural abundance are compensated by the overlap of flavin and protein signals. These bands are assigned to prominent conformational changes in the PHR by blue light illumination. We postulate that not only the partial unfolding of the C‐terminal extension but also changes in the PHR may mediate signaling events. Abstract : Conformational changes in the blue light receptor plant cryptochrome have been found in the C‐terminal extension (CCT), but few studies have addressed the changes in secondary structure in the sensory photolyase homology region (PHR). Here, we investigated the PHR by light‐induced infrared difference spectroscopy after establishing a global 13 C and 15 N labeling that preserves the chromophore flavin at natural abundance. As a result, difference bands are revealed that are assigned to prominent conformational changes in the PHR by illumination. We postulate that in addition to those in the CCT also changes in the PHR may mediate signaling events.